Care seeking and treatment for hepatitis C infection in Rwanda: A qualitative study of patient experiences. Issue 12 (1st December 2020) - Van Nuil, Jennifer Ilo; Shumbusho, Fabienne; Kateera, Fredrick; Mukuralinda, Alain; Kabahizi, Jules; Muvunyi, Claude Mambo; Musabeyezu, Emmanuel; Mukabatsinda, Constance; Mbituyumuremi, Aimable; Nsanzimana, Sabin; Mukerjee, Joia; Gupta, Neil
ABSTRACT: An estimated 71 million people live with hepatitis C virus (HCV) and without an effective vaccination, control efforts depend entirely on prevention, early diagnosis, and treatment with direct acting antiviral medication. The experiences of accessing care and treatment, as well as how HCV is locally perceived, are context specific and require an understanding of local epidemics. The objectives of this study were to explore the experiences and demand-side barriers for people with chronic HCV infection, as well as describe the social and cultural landscapes in which they experienced, managed, and perceived HCV in Rwanda. Eleven participants provided consent to participate and all completed two semi-structured interviews during treatment within a clinical trial. We identified four themes: (1) diagnosis and use of traditional medicine, (2) access and financial barriers, (3) complex social networks (4) proactivity in care-seeking. Results demonstrate the complex ways in which Rwandans understand HCV, utilise parallel health systems, activate social networks, and the importance of active agency in the opportunities and outcomes for their own health in the context of an early response to a major epidemic. Without recognising communities' understanding and expectations, it is impossible to build a sustainable and successful public health response to HCV.